Association Between Stress and Coping with DNA Methylation of Blood Pressure-Related Genes Among African American Women. (September 2019) - Brown, Kristen M.; Hui, Qin; Huang, Yunfeng; Taylor, Jacquelyn Y.; Prescott, Laura; Barcelona de Mendoza, Veronica; Crusto, Cindy; Sun, Yan V.
Background: Exposure to psychosocial stress and employment of high effort coping strategies have been identified as risk factors that may partially explain the high prevalence of hypertension among African Americans. One biological mechanism through which stress and coping may affect risk of hypertension is via epigenetic modifications (e.g., DNA methylation) in blood pressure-related genes; however, this area remains understudied in African Americans. Methods: We used data from the ongoing Intergenerational Blood Pressure Study, a longitudinal study designed to investigate factors that contribute to hypertension risk in African American women (n = 120) and their young children, to investigate the association between stress overload, problem-solving coping, avoidance coping, and social support coping with DNA methylation in 25 candidate genes related to blood pressure. Multivariable linear regression and multilevel modeling were used to conduct methylation site-level and gene-level analyses, respectively. Results: In site-level analyses, stress overload, problem-solving coping, social support coping, and avoidance coping were associated with 47, 63, 66, and 61 sites, respectively, at p < 0.05. However, no associations were statistically significant after multiple testing correction. There were also no significant associations in gene-level analyses. Conclusions: As human social epigenomics is an emerging, evolving area of research, there is much to be learned from studies with statistically significant findings as well as studies with null findings. Factors such as characteristics of the social stressor, source of DNA, and synchronization of exposure and outcome are likely important considerations as we move the field forward.